2011
DOI: 10.1105/tpc.111.088906
|View full text |Cite
|
Sign up to set email alerts
|

Nonessential Plastid-Encoded Ribosomal Proteins in Tobacco: A Developmental Role for Plastid Translation and Implications for Reductive Genome Evolution  

Abstract: Plastid genomes of higher plants contain a conserved set of ribosomal protein genes. Although plastid translational activity is essential for cell survival in tobacco (Nicotiana tabacum), individual plastid ribosomal proteins can be nonessential. Candidates for nonessential plastid ribosomal proteins are ribosomal proteins identified as nonessential in bacteria and those whose genes were lost from the highly reduced plastid genomes of nonphotosynthetic plastid-bearing lineages (parasitic plants, apicomplexan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(164 citation statements)
references
References 80 publications
8
149
0
1
Order By: Relevance
“…Dysfunctional plastids caused other developmental abnormalities that are consistent with plastid signals contributing to development, such as pale and elongated leaves, reduced apical dominance [68] and lack of aerial organ development [69]. Blocking chloroplast biogenesis with a norflurazon treatment appeared to affect leaf size in part by inhibiting the transition from cell-proliferation-based morphogenesis to cell-expansion-based morphogenesis [38].…”
Section: Plastid Signals Contribute To Developmentmentioning
confidence: 97%
“…Dysfunctional plastids caused other developmental abnormalities that are consistent with plastid signals contributing to development, such as pale and elongated leaves, reduced apical dominance [68] and lack of aerial organ development [69]. Blocking chloroplast biogenesis with a norflurazon treatment appeared to affect leaf size in part by inhibiting the transition from cell-proliferation-based morphogenesis to cell-expansion-based morphogenesis [38].…”
Section: Plastid Signals Contribute To Developmentmentioning
confidence: 97%
“…In this respect, reverse genetic analysis in tobacco revealed that inactivation of the chloroplast ribosomal protein genes rps15 and rpl36 gave rise to homoplasmic transplastomic lines, indicating that these proteins are nonessential (Fleischmann et al, 2011). However, photosynthetic activity and growth were strongly impaired in the absence of Rpl36 and affected to a lesser extent in the absence of Rps15, indicating that translational activity is decreased in the absence of either of these two proteins.…”
Section: Loss Of Chloroplast Translation Leads To An Arrest In Cell Gmentioning
confidence: 99%
“…The hybridization probe used for DNA gel blot analysis (derived from the psaJ coding region) is also indicated. (B) Map of the genomic region containing rps15 and map of the transformed plastid genome in Drps15 mutants (Fleischmann et al, 2011). In the Drps15 single mutant and the Drps15/Drpl36 double knockout, the spectinomycin resistance marker aadA disrupts the rps15 gene, whereas in the Drps15/Drpl33 plants, rps15 is inactivated with the kanamycin resistance gene aphA-6 (Huang et al, 2002).…”
Section: Construction Of Transplastomic Double Knockout Plants For Thmentioning
confidence: 99%
“…Not all components of the 70S ribosome are essential for translation; in both bacteria and plastids, several ribosomal proteins have been identified as nonessential (Baba et al, 2006;Rogalski et al, 2008;Fleischmann et al, 2011). The genes for the Rps15 protein (S15) of the small ribosomal subunit and the Rpl33 (L33) and Rpl36 (L36) proteins of the large ribosomal subunit can be inactivated in E. coli (Maguire and Wild, 1997;Ikegami et al, 2005;Ikegami et al, 2005) and in plastids (Rogalski et al, 2008;Fleischmann et al, 2011) without losing viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation